Large-scale synthesis of van der Waals 1-dimensional material Mo6S3I6 by using a MoI2 precursor - Oh, Seungbae; Chae, Sudong; Choi, Kyung Hwan; Kim, Bum Jun; Lee, Sang Hoon; Wang, Cong; Liu, Zhixiang; Jeon, Jiho; Lee, Jae Hyun; Yu, Hak Ki; Choi, Jae Young (Journal of Alloys and Compounds, 2019)
By using a MoI2 precursor, a one-dimensional linear chain material, Mo6S3I6, was synthesized on a centimeter scale. As MoI2 can be used to form Mo6S3I6 through a gas-phase reaction, a larger amount of single crystals can be synthesized; moreover, these crystals are significantly longer than those synthesized by using Mo, S, and I powder. The synthesized Mo6S3I6 exhibited the characteristics of paramagnetic semiconductors with excellent thermal stability and a low bandgap. Furthermore, Mo6S3I6 can be separated into long nanometer-scale chains by a solution dispersion process.
Keywords: 1D materials; Centimeter-scale; Dispersion process; Gas-phase reactions; Large scale synthesis; Mo6S3I6; MoI2 precursor; Nano-meter scale; 1D materials; Centimeter-scale synthesis; Mo6S3I6; MoI2 precursor